2015
DOI: 10.3899/jrheum.141243
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experience of Myositis and Further Validation of a Myositis-specific Patient Reported Outcome Measure — Establishing Core Domains and Expanding Patient Input on Clinical Assessment in Myositis. Report from OMERACT 12

Abstract: The currently used PROM do not assess symptoms or the effects of disease that are most important to patients; this emphasizes the necessity of patient involvement. Our work provides concrete examples for PRO identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Based on the qualitative content analysis of transcripts from the 11 focus groups involving 66 participants from 3 countries, an initial list of 26 candidate domains was constructed (12,13). During discussions between SIG investigators and PRPs, content and wording of the items for the first round online modified Delphi were revised until they best reflected the original intended domains and subdomains and would be comprehensible by patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the qualitative content analysis of transcripts from the 11 focus groups involving 66 participants from 3 countries, an initial list of 26 candidate domains was constructed (12,13). During discussions between SIG investigators and PRPs, content and wording of the items for the first round online modified Delphi were revised until they best reflected the original intended domains and subdomains and would be comprehensible by patients.…”
Section: Methodsmentioning
confidence: 99%
“…To study patients’ experiences of disease we previously reported the results of several focus group sessions conducted in three countries, and analyzed transcripts to identify domains that were described by patients as relevant to their experience of myositis (12). These results were presented at the OMERACT meeting in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…High-level themes included pain, physical stiffness or loss of flexibility, fatigue, emotional impact, the effect of the disease on relationships and treatment-related side effects [103]. The Myositis Activities Profile (MAP), a 31 item disease-specific questionnaire with 4 subscales of movement, social, self-care, domestic and leisure activities was examined by the OMERACT group and also taken back to the patients in individual interviews using the “think aloud” technique, leading to a revised MAP that will be tested by Rasch methodology to optimize subscale and scoring and eliminate redundancy [104] (Table 2). …”
Section: Evaluation Of Quality Of Life (Qol) In Iimmentioning
confidence: 99%
“…Based on the qualitative content analysis of transcripts from the 11 focus groups involving 66 participants from 3 countries, an initial list of 26 candidate domains was constructed 12,13 . During discussions between SIG investigators and PRP, content and wording of the items for the first round online modified Delphi were revised until they best reflected the original intended domains and subdomains and would be comprehensible by patients.…”
Section: Methodsmentioning
confidence: 99%
“…To study patients' experiences of disease, we previously reported the results of several focus group sessions conducted in 3 countries, and analyzed transcripts to identify domains that were described by patients as relevant to their experience of myositis 12 . These results were presented at the OMERACT meeting in 2014.…”
mentioning
confidence: 99%